Assessment, Selection, Use, and Evaluation of Body-Worn Absorbent Products for Adults With Incontinence: A WOCN Society Consensus Conference. Issue 3 (May 2018) - Gray, Mikel; Kent, Dea; Ermer-Seltun, JoAnn; McNichol, Laurie
Abstract : The Wound, Ostomy and Continence Nurses (WOCN) Society charged a task force with creating recommendations for assessment, selection, use, and evaluation of body-worn absorbent products. The 3-member task force, assisted by a moderator with knowledge of this area of care, completed a scoping literature review to identify recommendations supported by adequate research to qualify as evidence-based, and area of care where evidence needed to guide care was missing. Based on findings of this scoping review, the Society then convened a panel of experts to develop consensus statements guiding assessment, use, and evaluation of the effect of body-worn absorbent products for adults with urinary and/or fecal incontinence. These consensus-based statements underwent a second round of content validation using a modified Delphi technique using a different panel of clinicians with expertise in this area of care. This article reports on the scoping review and subsequent evidence-based statements, along with generation and validation of consensus-based statements that will be used to create an algorithm to aid clinical decision making.